A systematic review of the literature reveals trends and gaps in integrated pest management studies conducted in the United States. Issue 8 (26th April 2017) - Young, Stephen L
Abstract: Integrated pest management (IPM) is a broad‐based approach for addressing pests that negatively affect human and environmental health and economic profitability. Weeds, insects and disease‐causing pathogens (diseases) are the pests most often associated with IPM. A systematic review, widely used in other scientific disciplines, was employed to determine the most commonly studied IPM topics and summarize the reasons for these trends and the gaps. In a field synopsis of the literature, 1679 relevant published papers were identified and categorized into one of the following five broad areas: IPM and organic (organic), climate change and pests (climate), rural and urban IPM (rural and urban), next‐generation education (education) and advanced production systems (technology). Papers were examined in greater detail for at least one of the three main pests in a systematic review. A majority (85%) of IPM papers have been in the area of rural and urban IPM, primarily addressing agriculture (78%). Professionals, landowners and the general public were the focus of a majority (95%) of IPM papers on education. Technology is an increasing area of focus in the literature. Over the past 40 years, IPM papers have primarily (75%) addressed insects and been limited mostly to rural and urban settings. Climate change, technology and education specific to pest management studies are increasingly being published and will help broaden the focus that could result in increased adoption and development of IPM. © 2017 Society of Chemical Industry